Comparison of Reconstruction Strategies of Compressive Sensing Applied to Ultrasound Images - TOLEDO, ERICK (SPRINGER, 2018)
Ultrasound medical images are important for medical diagnose. The method allows the real-time visualization of organs of the body and it is not invasive. In this study, a comparison of reconstruction greedy search methods, used in compressive sensing, is performed. The methods and the algorithms are explained and experiments are carried out in synthetic and measured data. Result show that the orthogonal matching pursuit outperforms the other methods in the greedy search classification.